A novel computer vision‐based assessment of neutrophil chemotaxis in patients with severe infection. Issue 8 (18th August 2021) - Yang, Yunxi; Liu, Lu; Guo, Zaiwen; Huang, Jiamin; Li, Linbin; Shao, Yiming; Song, Mingming; Yang, Aixiang; Sun, Bingwei
Abstract: Objectives: To evaluate the value of chemotactic function of neutrophils in patients with severe infections. Methods: A computer vision‐based cellular chemotaxis analysis platform was established for the dynamic assessment of neutrophil chemotaxis. Fifty‐three patients in the intensive care unit were eligible for the study. In parallel, 142 healthy volunteers were recruited to detect and establish the normal values for chemotactic function. Four chemotactic function indicators were determined–chemotaxis distance (CD), chemotaxis cell ratio (CCR), chemotaxis index (CI) and maximum speed of chemotaxis (Vmax ). The chemotaxis function scores (CFS) were calculated for further correlation analysis with clinical data. Results: The normal ranges of indicators were established as CD ≥ 1755.85 µm, CCR ≥ 3.34%, CI ≥ 39.63, Vmax ≥ 14.63 µm min −1 and CFS ≥ 15. We found that the chemotactic function of neutrophils in patients suffering from infections was significantly impaired. The mean values of CD, CCR, CI, Vmax and CFS were 1452.8 µm ( P < 0.0001), 3.1% ( P < 0.0001), 34.5 ( P < 0.0001), 12.2 µm min −1 ( P < 0.0001) and 9 ( P < 0.0001), respectively. CD and CFS were significantly negatively correlated with the APACHE II score (rCD = −0.55, rCFS = −0.39), SOFA score (rCD = −0.68, rCFS = −0.56), procalcitonin concentration (rCD = −0.60, rCFS = −0.5) and the expression of P2RX1 (rCD = −0.76, rCFS = −0.56), respectively. Conclusions: CD, CCR, CI and Vmax can well reflect the neutrophil chemotactic function in patients with severe infections. CFS systematically indicated neutrophil function and has promising clinical application prospects. Abstract : In this study, we focused on patients with severe infection in the intensive care unit (ICU) and accurately evaluated their neutrophil chemotactic function. We developed a platform, the 'Cell Chemotaxis Analysis Platform based on Computer Vision' (CCAP), and critically assessed the chemotactic function of neutrophils in 53 ICU patients with severe infection by the improved agarose gel chemotactic model and detected the expression of P2RX1 on the surface of PMN synchronously. For the first time, we accurately revealed the dynamic changes in PMN chemotactic function in patients with severe infection and provided novel evaluation indexes and a potential biomarker for clinical treatment.